Adiabatic index of hot and cold compact objects - Casali,R. H. (2010)
In the present work we calculate the adiabatic index of neutron stars formed by hadronic or quarkionic matter, under two possible conditions, with and without trapped neutrinos, and for two values of the entropy per baryon S = 0,2 kB/ baryon. We use the nonlinear Walecka model to describe hadronic stars, and the MIT bag model to describe quark stars. Particle fractions for each case are obtained and the appearance of particles are compared with drops in the adiabatic index, whenever possible.